Public Trust and Consumer Loyalty Towards Consumer Interest in Revisiting Kamu Desa Denai Lama, Deli Serdang District - Erianto, Edy; Hanafi, Muhammad Hirsan; Lubis, Sri Rosliana; Siregar, Mhd Daud (International Journal of Economics and Management, 2024)
Pasar Kamu Desa Denai Lama is one of the interesting tourist attractions in Deli Serdang Regency. It has a unique appeal as it offers visitors a traditional shopping experience that involves the local culture. The market is also the perfect place to sample typical Deli Serdang food. Pasar Kamu Desa Denai Lama is also often a tourist spot for cultural festivals or special events. It offers art and cultural performances, handicraft exhibitions, and other traditional activities. Conventional markets, however, sometimes face competition from contemporary retail, shopping centers, or online shopping platforms. In order to survive and thrive amidst the competition, it is imperative for the Kamu Desa Denai Lama market to increase customer interest in revisiting. Research focused on the factors that influence customer interest in returning to the market should be conducted to solve this problem. The level of public trust and consumer loyalty are two important components in increasing customer interest in returning. This research uses a quantitative approach to analyze. where data in the form of numbers is processed and analyzed to produce scientific information. Public Trust in Your Market Desa Denai Lama, or public trust, has a major influence on customers' desire to return. If customers feel trust and yes.